2018
DOI: 10.1002/lary.27271
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of left–right vocal fold symmetry in rheological and histological properties

Abstract: NA. Laryngoscope, 128:E359-E364, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We also found that if the correlations among rheological data are ignored during statistical analysis, type I errors will be substantially inflated. Although it was previously noted that the widely used regression-fitting methods are not suitable for the statistical analysis of data generated from repeated measurements (Xu et al, 2017;Xu et al, 2018), the current study demonstrated for the first time exactly how such inappropriate statistical methods affect the outcome of vocal fold rheological data analysis.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…We also found that if the correlations among rheological data are ignored during statistical analysis, type I errors will be substantially inflated. Although it was previously noted that the widely used regression-fitting methods are not suitable for the statistical analysis of data generated from repeated measurements (Xu et al, 2017;Xu et al, 2018), the current study demonstrated for the first time exactly how such inappropriate statistical methods affect the outcome of vocal fold rheological data analysis.…”
Section: Discussionmentioning
confidence: 69%
“…As shown in Table 1, frequency is always one of the fixed effects in the models because G' and η' are functions of frequency. Our recent study also showed that it was preferable to treat frequency as a categorical variable (Xu et al, 2018). Another fixed effect is the treatment effect, for the assessment of possible significant relationship between tissue rheological properties and a treatment.…”
Section: 11mentioning
confidence: 95%
See 3 more Smart Citations